Korelasi Tingkat Kepatuhan Pengobatan terhadap Kadar Glukosa Darah pada Pasien Geriatri Diabetes Melitus Tipe 2 di Puskesmas Kota Padang: Correlation of Medication Adherence to Blood Glucose Levels among Geriatric Patients with Type 2 DM at Health Center in Padang - widya kardela; Endang Agustina; Rangti A. Harartasyahrani; Rezlie Bellatasie (LPPM Universitas Abdurrab, 2023)
Uncontrolled blood glucose levels in DM patients can cause various microvascular and macrovascular complications. One of the main problems causing uncontrolled blood glucose in type 2 DM patients is non-adherence to medication therapy, especially in geriatric patients. This study aims to assess the rate of medication adherence and blood glucose levels, then to analyze the relationship between the rate of medication adherence and blood glucose levels among geriatric patients with type 2 DM at the Nanggalo Health Center, Padang. Medication adherence was assessed using the ARMS-D questionnaire which had been tested for validity and reliability. Prospective data collection using a cross-sectional quantitative design with purposive sampling technique, data were analyzed by fisher's exact test. The results showed that of the 45 patients, most were classified as suboptimal adherence patients (82.2%), and the majority of patients had uncontrolled blood glucose levels (62.2%). Based on the results of the correlation test, the value of p = 0.003 (p <0.05). Hence, there is a significant relationship between the rate of medication adherence and blood glucose levels among geriatric patients with type 2 DM at the Nanggalo Health Center, Padang.